FATWA MUI TENTANG VASEKTOMI Tanggapan Ulama dan Dampaknya terhadap Peningkatan Medis Operasi Pria (MOP) - Muhyiddin, Muhyiddin (Al-Ahkam, 2014)
This field research aims to determine three things: the background of the changing fatwa  MUI on Vasectomy from ‘haram’ to ‘halal on condition’; responses from the Moslem scholars; and the impact of fatwa on increasing the number of Vasectomy participants in Central Java. The data collection was done by using documentation and interviews while data analysis was done by using descriptive qualitative method. The results of this research are: 1) The reason for the changing fatwa on Vasectomy from ‘haram’ to ‘halal on condition’ is due to a new ‘illat, namely the success of recanalization. 2) Against the new fatwa, Ulama Muhammadiyah approved it by tightening and adding certain requirements. While Ulama NU disagree on the fatwa as evidence of the success of recanalization is considered not convincing (muhaqqaqah). 3) The new fatwa has not been an impact on increasing the number of Vasectomy participants in Central Java.